A New Theology for a New Society in Empedocles's Verses - Casella, Federico (Revista Archai, 2025)
The aim of this paper is to analyze Empedocles’s main doctrines in the light of his historical and cultural context. To be precise, I will attempt to show how the Agrigentum and Sicily of his time - ravaged by inter-Greek wars, infighting between the various social classes, and even indigenous Sicilians’ revolts against Greek settlers - bore witness, in his eyes, to the ever-increasing power of Strife, which was influencing the cosmos not solely on a physical level but also on a moral one. Empedocles hoped in the exit from the present cosmic cycle through the attainment of a higher condition, capable of transforming the daimones into ‘holy minds’, i.e. into entities completely imbued with Love and, for this reason, unassailable by Strife in this cosmic phase, well before the return of the sphere. In this way, Empedocles tried to found a new theology, with Love as the main deity, and a new ethical code, in opposition to traditional poems and values, which were the expression, as everything else in the world save for his On nature and Purifications, of Strife.